PENINGKATAN MANEJEMEN KEUANGAN MASYARAKAT DESA CIMANGGU 1 MELALUI SOSIALISASI PENGGUNAAN M-BANKING DAN BAHAYA PINJAMAN ONLINE - Nurjanah, Nurjanah; Alfin, Alfin; Achmad, Dinda Zivarulia; Fathimah, Eva Aurelia; Pamulatsih, Wening; Eriyani, Eni; Kurniawan, Bobby; Syaifulloh, Syaifulloh; Qothrunnada, Haniyah; Gemilang, Raihan; Amelia, Khayrani; Alamsyah, Muhamad Rizki (LPPM Institut Pendidikan Nusantara Global, 2024)
Social Work Lecture (KKS) is an applicable activity, namely implementing lecture material into social activities in the field. One of the main focuses in this service is providing training on financial management to the community of Cimanggu 1 Village. This activity involves FAI UHAMKA students as the implementing committee and the community as the object of the activity. It is hoped that the presence of this service will provide additional knowledge about how to manage finances well using M-Banking and be careful with online loans.